Failure by design: lessons from the recently rescinded light brown apple moth (Epiphyas postvittana) eradication program in California. Issue 3 (15th November 2022) - Carey, James R.; Harder, Daniel; Zalom, Frank; Wishner, Nan
Abstract: This article was motivated by the US Department of Agriculture (USDA) Animal and Plant Health Inspection Service (APHIS) announcement that on 17 December 2021 it rescinded Federal Orders of 2 May 2007 that regulated (what was believed to be) a new outbreak of the light brown apple moth (LBAM, Epiphyas postvittana (Walker)) in the mainland United States. Our article follows from, and builds on, a 2013 article published by Carey and Harder that outlined major concerns about the LBAM eradication program including the need, cost, safety, practicality, and feasibility of the program and the public opposition to it. The program began with an emergency order based on USDA claims of billions of dollars in potential crop losses and the need to circumvent safety review processes to urgently prevent the pest's establishment. The program ended with the realization by government decision‐makers, 14 years after initiating the program, that LBAM posed no quarantine‐level threat in the first place and with no evidence of any economic damage done by the insect. This article summarizes the mistakes made in devising and carrying out what has ultimately proven to be one of the most oversold, overhyped, misguided, ill‐advised, unnecessary, and costly programs in the recent history of insect eradication programs in California. Termination of the LBAM program by USDA‐APHIS presents an opportunity to review the program to identify lessons learned and provide recommendations to help avoid similar mistakes in future invasive species response programs. © 2022 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : This article summarizes the mistakes made in devising and carrying out the 2007–2021 light brown apple moth eradication program in California, a program that was ultimately proven to be one of the most oversold, misguided, ill‐advised and costly programs in the recent history of insect eradication programs in California.